Impact of student exclusion (including from the SPE) on their digitisation behaviour in social media - Prościak, Marcin; Prościak, Beata (Journal of Education Culture and Society, 2020)
Aim. The aim of this thesis is to present the impact of students exclusion (including SPEs) on their virtual behaviour in social media. Students with no special educational needs and those with SEN were taken into account. The relationship between exclusion of SPE and digitisation exclusion will be indicated . In addition, social exclusion in the family area was included. Methods: The analysis was based on statistical methods, such as: range, standard deviation, variance. Surveys were used. They were conducted on the Internet through the Facebook social portal on a national and global scale. Results: Respondents from around the world feel more excluded by the SPE than respondents in Poland. In contrast, respondents from the SPE use fewer social networking sites than in groups of computer players, both in Poland and worldwide. Conclusions: In Poland, SPE is not a barrier to communication with peers for most respondents, unlike global respondents. Respondents from the SPE spend less time on social portals because it absorbs their time devoted to learning, which can be an indicator of digital exclusion. Cognitive value: The originality of the research is to focus on introducing the global and Polish scale of the problem excluding students from SPE from the social media, which was calculated by the author’s method based on the indicator digital exclusion.